Empowerment Community: Pembentukan Komunitas Peduli Lingkungan Sebagai Upaya Peningkatan Kesadaran Bencana & Kesehatan Pada Warga Bantar Kali Di Kampung Payung Kertas, Malang - Lusy Asa Akhrani; Ika Herani; Alfrina Hany (Journal of Dedicators Community, 2021)
Payung Kertas Village located at Pandanwangi Village, on the bank of the Bango river. The preliminary research showed that the environmental care behavior of residents of the riverbank area is to be low considering. Many residents choose to throw garbage directly in the river, construction residential houses in the Kali Sari watershed, and several indicator of the lack of environmental awareness of watershed residents. Awareness-raising will be easier to do when activities are started, designed, and carried out by communities with social problems. The aims of this community service is to empower communities to solve social problems. The formation of environmentally conscious communities is carried out through a tiered process by encouraging active citizen involvement. The method used in the fomation rof environmental care communities is carried out with a social intervention approach that utilizes action research. Social change is carried out by emphasizing three stages namely the planning, implementation, and evaluation stages. As a result of this community service, a community caring for the environment was formed with the first movement in the form of sorting waste from inside the house, synergizing with waste transport officers, and periodically monitoring and evaluating the implementation of the environmental care movement.